Dialectics of Public Reading of Scriptures: An Intersectional Study of the Bhagavad Gita and the Gospel of John - Paul Rohan, J.C. (Global Network for Public Theology, 2025)
Public theology, which interprets sacred texts within societal contexts, requires a significant approach to read and apply them in the public sphere. This paper explores the dialectics of public reading of the Bhagavad Gita and the Gospel of John, the foundational texts of Hindu and Christian traditions. The Bhagavad Gita offers guidance on righteous living and spiritual enlightenment through Krishna’s teachings to Arjuna on the battlefield of ‘Kurukshetra’. Addressing paths to liberation, Krishna urges Arjuna to align personal duty with cosmic order, portraying ethical living as an expression of divine will. The Gospel of John emphasizes the divinity of Jesus Christ as the eternal ‘Logos’. Through teachings on faith, love, and obedience to God, Jesus reveals the transcendent reality and invites the followers to fulfil their divine purpose, presenting himself as the path to salvation. This study uses intra and inter-textual analysis, along with a historico-critical approach, to examine thematic coherence within each text and the dialogues between them. Despite differing origins, both texts share themes of duty, divine will, and ethical responsibility. Krishna’s guidance to Arjuna and Jesus’s teachings to Peter and the disciples emphasize aligning human life with divine purpose, offering insights into a universal quest for meaning. The hypothesis emerges that, despite unique theological orientations, the Bhagavad Gita and the Gospel of John promote a shared ethical trajectory supporting communal wellbeing. In Asia’s multi-religious context, this dialogical approach to the sacred texts fosters interfaith cooperation and shared values to provide pathways for mutual understanding and collaborative action to form a just and harmonious society. It will also cultivate a shared moral language to equip public theology to guide communities towards integrity and compassion.
Keywords: Dialogical; Divine will; Interfaith; Ethical trajectory; Devotion